An optimal design analysis of a novel parabolic trough lighting and thermal system. (6th March 2016) - Li, Tonghui; Yuan, Chris
Summary: In order to reduce the cost and improve the efficiency of daylighting, an innovative parabolic trough solar lighting and thermal (PTL/T) system is designed and analyzed in this paper. Parabolic trough solar lighting and thermal system uses parabolic trough collector (PTC) controlled by two‐axis solar tracking system as solar collector. The collected sunlight is split by a cold mirror into visible light and infrared. The visible light is reflected by cold mirror, re‐concentrated by a second‐stage Fresnel lens, and then delivered by plastic optical fiber to the buildings for daylighting. The infrared goes through cold mirror, reaches thermal system, and is used for heating generation. The basic structure of PTL/T was outlined and described. The dimension of fiber bundle and parabolic trough was chosen after an optimal analysis. The cost of illuminating unit area was expressed as a function of illumination space dimensions and critical components efficiency. A case study was conducted to get a specific optimized illumination area and PTC area for the first time. The optimized result is to use 8‐m 2 PTC as collector to illuminate 500‐m 2 office space. The total solar energy utilization efficiency is 39.4%, with the lighting efficiency of 16.3% and thermal efficiency of 23.1%. The maximum energy savings and simple payback period were calculated for 10 typical cities when applied in residential, commercial, and industrial sectors. The amounts of greenhouse gas‐emission reductions were also calculated. The payback period in Sunbelt region is as low as less than 10 years like in Los Angeles. The results show the proposed PTL/T system is competitive compared with traditional solar energy systems. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Parabolic trough solar collector is proposed to be used in daylighting system. Daylighting and thermal system are combined together in the proposed Parabolic Trough Lighting and Thermal System (PTL/T) for the first time. The basic structure of PTL/T is outlined and described. The cost of illuminating unit area is functionalized. The illumination area is optimized based on energy savings and economic analysis in a case study.